The Photomorphogenic Transcription Factor PpHY5 Regulates Anthocyanin Accumulation in Response to UVA and UVB Irradiation - Zhao, Yun; Min, Ting; Chen, Miaojin; Wang, Hongxun; Zhu, Changqing; Jin, Rong; Allan, Andrew C.; Lin-Wang, Kui; Xu, Changjie (Frontiers in Plant Science, 2021)
Red coloration contributes to fruit quality and is determined by anthocyanin content in peach. Our previous study illustrated that anthocyanin accumulation is strongly regulated by light, and the effect of induction differs according to light quality. Here we showed that both UVA and UVB irradiation promoted anthocyanin biosynthesis in ‘Hujingmilu’ peach fruit, and a combination of UVA and UVB had additional effects. The expression of anthocyanin biosynthesis and light signaling related genes, including transcription factor genes and light signaling elements, were induced following UV irradiation as early as 6 h post-treatment, earlier than apparent change in coloration which occurred at 72 h. To investigate the molecular mechanisms for UVA- and UVB-induced anthocyanin accumulation, the genes encoding ELONGATED HYPOCOTYL 5 (HY5), CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1), Cryptochrome (CRY) and UV RESISTANCE LOCUS 8 (UVR8) in peach were isolated and characterized through functional complementation in corresponding Arabidopsis mutants. PpHY5 and PpCOP1.1 restored hypocotyl elongation and anthocyanin content in Arabidopsis mutants under white light; while PpCRY1 and PpUVR8.1 restored AtHY5 expression in Arabidopsis mutants in response to UV irradiation. Arabidopsis PpHY5/hy5 transgenic lines accumulated higher amounts of anthocyanin under UV supplementation (compared with white light only), especially when UVA and UVB were applied together. These data indicates that PpHY5, acting as AtHY5 counterpart, was a vital regulator in UVA and UVB signaling pathway. In peach, the expression of PpHY5 was up-regulated by UVA and UVB, and PpHY5 positively regulated both its own transcription by interacting with an E-box in its own promoter, and activated the transcription of the downstream anthocyanin biosynthetic genes PpCHS1, PpCHS2 and PpDFR1 as well as the transcription factor gene PpMYB10.1. In summary, functional evidence supports a role of PpHY5 in UVA and UVB light transduction pathway controlling anthocyanin biosynthesis in peach fruit. This is via up-regulation of expression of genes encoding biosynthetic enzymes, as well as the transcription factor PpMYB10.1 and PpHY5 itself.